1998
DOI: 10.1562/0031-8655(1998)068<0141:pacada>2.3.co;2
|View full text |Cite
|
Sign up to set email alerts
|

PhotochemCAD††: A Computer-Aided Design and Research Tool in Photochemistry

Abstract: A database of absorption and fluorescence spectra, including molar absorption coefficients and fluorescence quantum yields, has been compiled for 125 photochemically relevant compounds. An accompanying program enables calculation of oscillator strengths, natural radiative lifetimes, transition dipole moments, Forster energy-transfer rates, multicomponent analysis, simulations of fluorescence spectra upon energy transfer among linear arrays of pigments, calculations of blackbody radiator curves at different tem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
175
0
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 162 publications
(184 citation statements)
references
References 1 publication
8
175
0
1
Order By: Relevance
“…We now measured the fluorescence spectra of the test compounds 1-3 in phosphate buffered saline (PBS; 5 µM) at pH 7.4. Since the fluorophore of 1 has a known absorption maximum between 480 nm and 500 nm [14] we excited the test compounds at 490 nm and observed three congruent fluorescence spectra (Fig. 2).…”
Section: Fluorescence Spectroscopymentioning
confidence: 99%
“…We now measured the fluorescence spectra of the test compounds 1-3 in phosphate buffered saline (PBS; 5 µM) at pH 7.4. Since the fluorophore of 1 has a known absorption maximum between 480 nm and 500 nm [14] we excited the test compounds at 490 nm and observed three congruent fluorescence spectra (Fig. 2).…”
Section: Fluorescence Spectroscopymentioning
confidence: 99%
“…For example, RhoB itself has its maximum absorbance around 543 nm. If a laser source operating near this wavelength had been available, the amount of RhoB needed would have been reduced because the molar absorption at 532.07 nm is 81 954 cm -1 M -1 , whereas it is 106 000 cm -1 M -1 at 543 nm (Du et al 1998).…”
Section: Discussionmentioning
confidence: 99%
“…RhoB displays a broad absorbance between 500 and 600 nm, and therefore absorbs light strongly at 532 nm (its molar absorption coefficient at the laser wavelength is 81 954 cm -1 M -1 ) (Du et al 1998), so we could minimize the dye concentration to avoid dye-related changes in the chemical and physical properties of the adsorbed water film. The theory on which this approach is based is the BeerLambert Law, which states that for light traveling through a sample solution, the absorbance (A), is proportional to the path length l, solution concentration c, and the molar absorption coefficient ε.…”
Section: Materials and Proceduresmentioning
confidence: 99%
“…Wild birds associate pre-and postingestive consequences with visual cues, and reliably integrate visual and gustatory experience with postingestive consequences to procure nutrients and avoid toxins (Werner et al, 2008c;Werner and Provenza, 2011). Whereas anthraquinone is an emodin purgative (Merck, 1991) and anthraquinone absorbs near-ultraviolet light (300-400 nm; Du et al, 1998) that is visible to most birds, anthraquinone is a quintessential avoidance-conditioning agent for wild birds ). Werner and Provenza (2011) suggested that an effective application strategy for avian repellents might include initial applications of a postingestive repellent (e.g., anthraquinone) and subsequent applications of a visual cue with spectral characteristics (e.g., near-ultraviolet absorbance) sufficiently similar to the repellent (Werner, 2009).…”
Section: Discussionmentioning
confidence: 99%